An evaluation of the management cost of patients in Nephrology Department in Outpatient Department from June 2017 to November 2017 in Hospital Sultanah Nora Ismail - Megad Mohd Nizar, Puteri Faten Fariheen; Zulkafli, Nur Saidatul Arisya (2018)
Chronic kidney diseases (CKD) have become a major health issues and has a high prevalence rates that is appear to be increasing. To address this issue, we evaluate the cost management of patient in Nephrology Department in Outpatient Department (OPD) in Hospital Sultanah Nora Ismail. The objectives of our study are to analyze the costs management spent for nephrology patients in Hospital Sultanah Nora Ismail and to study the trend of prescribing of medications under nephrology cases to estimate the future expected costs for new patients register. The data collection from Queue Management System (QMS), Pharmacy Information System (Phis), and electronic Master Catalogue was compared to corresponding estimates and trends for all chronic kidney diseases as well as for all diseases. Total management cost for patient under nephrology cases from June 2017 to November 2017 is RM1727,938.60 where the total number of nephrology patients within June 2017 to November 2017 are 7580. The results have been calculated and the average costs spent for each month from June 2017 until November 2017 is RM287,989.77. We successfully calculated the cost spend for nephrology cases to estimate the future cost for every patient registered under nephrology cases. Thus, this study may help in the future financial plan and avoid wastage.